PENGARUH SEMANGAT KERJA DAN PEMBERIAN BONUS TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA UD. SEHAT INDAH KOTA GORONTALO - Agus Susanto Naue (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2021)
This study aims to determine the effect of Morale and the Provision Of Bonuses on the work effectiveness of employees at UD. Sehat Indah Gorontalo City either simultaneously or partially. This study used 49 employees as respondents where the questionnaire was used as a tool to obtain the main data to be analyzed using the SPSS version 21 analysis tool.Sehat Indah Gorontalo City with a large effect of 0.966 or 96.6%. Partially, Morale has a positive and significant effect on the effectiveness of employees' work at UD. Sehat Indah Gorontalo City with a large effect of 0.435 or 43.5% and partial Provision of Bonuses giving a positive and significant effect on the work effectiveness of employees at UD. Sehat Indah Gorontalo city by 0.549 or 54.9%. there are variables that are not examined but have an effect that is equal to 0.034.